Analisis Koordinasi Sistem Proteksi Trafo Distribusi 20 KV (Studi Kasus PT. PLN PERSERO Unit Lamongan) - Nahdia Rupawanti BR (Universitas Islam Lamongan, 2019)
Electric power distribution systems that use air cables or ground cables often experience various disturbances. Interference that often occurs is symmetry or non-symmetric interference which can be a short relationship between one phase to the ground, between phases or the breakdown of one or more. To find out the magnitude of the interference current, an analysis of the transformer distribution system is needed to determine the disturbances that will occur.The transformer which is the main equipment in a GI must be considered in order to get the proper current circuit and security. Designing the right transformer setting is an effort to protect equipment, systems and consumer needs from disturbances that may occur in the distribution system. The calculation of the fault current and the magnitude of the nominal current of the transformer will be used as an important reference in determining the transformer settings in the distribution of voltage to consumers.From the results of these calculations it can be concluded that the performance time of feeder relays is slower than the time of relay in the event. The data in the field is still in the right condition (the difference is not too far), so that the overall OCR-GFR setting in the field is still in good condition.